Clinical simulation: a contribution to teaching and learning in the Obstetrics area - Altamirano-Droguett, Janet Elizabeth (2019)
This descriptive study presents a bibliographic review to determine the contribution of the types of clinical simulation: simulated patient training, role play, and full patient simulators in the learning of midwives and midwives in training. An exhaustive search of this topic was carried out in Scielo and Scopus indexed scientific journals; the Google scholar search engine and PubMed, in the international and national context, were used. The search showed a lack of research on this didactic technique in the area of Obstetrics. The focus of analysis and discussion is learning, in order to specify the value of clinical simulation in the development of generic and professional competences from an experiential, psychocultural and pedagogical perspective. Finally, this study concluded that clinical simulation is necessary to improve the safety and confidence of the students enrolled in the Obstetrics and Child Care programs when facing their professional practices with real patients. Even though the development of different types of learning has been described with the use of this technique, this teaching tool needs to be strengthened in the undergraduate training process, with the teaching staff as a facilitator of learning.